A Case of Criminal Abortion by a Quack (unqualified person) Supreme Court Views - Yadav, Mukesh; Rastogi , Pooja (Journal of Indian Academy of Forensic Medicine, 2015)
Unsafe abortion is one of the four main causes of maternal mortality and morbidity. One of the  reasons for unsafe abortion is because safe abortion services are frequently not available, even when  they are legal for a variety of indications in almost all countries including India. A case of alleged illicit sexual relations of an unmarried woman of 27 years and consequently  pregnancy and criminal abortion by an unqualified and inexperienced doctor came before the SC in  appeal. Accused doctor had been convicted and sentenced by the trial court for seven years along with  fine, concurred by the MP High Court. Case came before the SC in Appeal by the co-accused in this  case. Various issues related to provisions of Indian Penal Code (IPC), Medical Termination of Pregnancy  Act and Rules, qualification and experience of the doctor for MTP, Approval of the place for MTP, and  issue of conviction and sentence of alleged accused, etc. has been discussed to create awareness  among stakeholders to avoid further cases of criminal abortions in India. This may help in decreasing  maternal morbidity and mortality in India due to criminal abortions.
Keywords: Expert Opinion; Post-mortem; Criminal Abortion; MTP; Conviction; Appeal; Supreme Court; High Court; Trial Court; Common Intention; Cross-Examination; Trial; Pregnancy; Illicit Relations